Remote ischemic conditioning preserves cognition and motor coordination in a mouse model of traumatic brain injury. Issue 6 (December 2017) - Sandweiss, Alexander J.; Azim, Asad; Ibraheem, Kareem; Largent-Milnes, Tally M.; Rhee, Peter; Vanderah, Todd W.; Joseph, Bellal
Abstract : INTRODUCTION: Management of traumatic brain injury (TBI) is focused on minimizing or preventing secondary brain injury. Remote ischemic conditioning (RIC) is an established treatment modality that has been shown to improve patient outcomes in different clinical settings by influencing inflammatory insults. In a clinical trial, RIC showed amelioration of SB100 and neuron-specific enolase. The aim of our study was to further elucidate the mechanisms and outcome when applying RIC in a mouse model of traumatic brain injury. METHODS: We subjected 100 male C57BL mice to a closed-skull cortical-controlled impact injury. Two hours after the TBI, the animals were allocated to either the RIC group (n = 50) or the sham group (n = 50). By clamping the exposed femoral artery, we induced RIC by six 4-minute cycles of ischemia and reperfusion. Circulating levels of S100-B, neuron-specific enolase, and glial fibrillary acidic protein were measured at multiple time points. Animals were additionally observed daily for cognition and motor coordination via novel object recognition and rotarod. Brain sections were stained and evaluated for neuronal injury at post-TBI Day 5. RESULTS: The RIC animals had a significantly higher recognition index than did sham at 24, 48, and 72 hours after intervention. Rotarod latency was higher in the RIC animals compared to the sham animals at all-time points, and statistically significant at 120 hours after intervention. The RIC group demonstrated preserved cognitive function and motor coordination compared to the sham. On hematoxylin and eosin and immunohistochemical staining of brain sections, there was less area of neuronal degeneration and astrocytosis, respectively, in the RIC group compared to the sham group. There was no significant difference in systemic neuronal markers between the RIC and sham animals. CONCLUSION: Remote ischemic conditioning 2 hours after injury preserved cognitive functions and motor coordination in a mouse model of TBI. Remote ischemic conditioning can preserve viability of neurons and astrocytes after TBI and has potential as a clinically noninvasive and relatively easy method to improve outcome after TBI. LEVEL OF EVIDENCE: Therapeutic studies, randomized controlled trial, level I.